2004
DOI: 10.1590/s1678-77572004000300009
|View full text |Cite
|
Sign up to set email alerts
|

Retention of provisional crowns cemented with eight temporary cements: comparative study

Abstract: any temporary cements are commercially available; therefore, it is necessary to indicate them for each clinical requirement with regard to the tensile strength of prosthetic retainers. Thus, the purpose of this study was to compare the retention of provisional crowns cemented with eight temporary cements, over full crown preparations with standardized mechanical principles as height, taper, and length. For that purpose, eighty human first premolars received full crown preparation with standardized height and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
1
5
0
4
Order By: Relevance
“…The present study agrees with the last study because crowns cemented with HC presented greater retention than TB. Several studies showed that non-eugenol zinc oxide-based cements are the least retentive among temporary cements (22,23) especially when abutments were not prepared or rough (8), as in the present study.…”
Section: Fit and Cementation Of Provisional Crownssupporting
confidence: 71%
See 1 more Smart Citation
“…The present study agrees with the last study because crowns cemented with HC presented greater retention than TB. Several studies showed that non-eugenol zinc oxide-based cements are the least retentive among temporary cements (22,23) especially when abutments were not prepared or rough (8), as in the present study.…”
Section: Fit and Cementation Of Provisional Crownssupporting
confidence: 71%
“…On the other hand, there is no concern in the literature about the effect of the temporary luting agent. If there is a study relating difference of retention between calcium-hydroxide and non-eugenol zinc oxide-based cements (22), it is related Results are presented as mean (standard deviation). similarly in another study (10).…”
Section: Fit and Cementation Of Provisional Crownsmentioning
confidence: 99%
“…A study by Rego used standardized dental specimens. Teeth were prepared with a high-speed turbine coupled to a surveyor with articulated rod to standardize a 6o taper and 4 mm height; but it was not possible to obtain specimens of identical dimensions (area/volume) ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Do zabezpieczania zębów można stosować leki blokujące kanaliki zębinowe oraz korony tymczasowe. 6,7 Korony ochronne mocuje się na zębach za pomocą cementów tymczasowych: tlenkowo-cynkowo-eugenolowych, tlenkowo-cynkowych bez eugenolu, na bazie żywic oraz na bazie wodorotlenku wapnia, 6,8 których skład jak i właściwości opisano w tabeli 1.…”
Section: Wstępunclassified